An Active C-Terminally Truncated Form of Ca2+/Calmodulin-Dependent Protein Kinase Phosphatase-N (CaMKP-N/PPM1E). (7th August 2013) - Ishida, Atsuhiko; Tsumura, Kumiko; Oue, Megu; Takenaka, Yasuhiro; Shigeri, Yasushi; Goshima, Naoki; Ishihara, Yasuhiro; Hirano, Tetsuo; Baba, Hiromi; Sueyoshi, Noriyuki; Kameshita, Isamu; Yamazaki, Takeshi
Abstract : Ca 2+ /calmodulin-dependent protein kinase phosphatase (CaMKP/PPM1F) and its nuclear homolog CaMKP-N (PPM1E) are Ser/Thr protein phosphatases that belong to the PPM family. CaMKP-N is expressed in the brain and undergoes proteolytic processing to yield a C-terminally truncated form. The physiological significance of this processing, however, is not fully understood. Using a wheat-embryo cell-free protein expression system, we prepared human CaMKP-N (hCaMKP-N(WT)) and the truncated form, hCaMKP-N(1–559), to compare their enzymatic properties using a phosphopeptide substrate. The hCaMKP-N(1–559) exhibited a much higher V max value than the hCaMKP-N(WT) did, suggesting that the processing may be a regulatory mechanism to generate a more active species. The active form, hCaMKP-N(1–559), showed Mn 2+ or Mg 2+ -dependent phosphatase activity with a strong preference for phospho-Thr residues and was severely inhibited by NaF, but not by okadaic acid, calyculin A, or 1-amino-8-naphthol-2, 4-disulfonic acid, a specific inhibitor of CaMKP. It could bind to postsynaptic density and dephosphorylate the autophosphorylated Ca 2+ /calmodulin-dependent protein kinase II. Furthermore, it was inactivated by H2 O2 treatment, and the inactivation was completely reversed by treatment with DTT, implying that this process is reversibly regulated by oxidation/reduction. The truncated CaMKP-N may play an important physiological role in neuronal cells.